The Prognostic Value of Reticulated Platelets in Patients With Coronary Artery Disease: A Systematic Review and Meta-Analysis - Zhao, Yihan; Lai, Runmin; Zhang, Ying; Shi, Dazhuo (Frontiers in Cardiovascular Medicine, 2020)
Background: Reticulated platelets (RPs) represent the young population in the circulating platelet pool, indicating platelet turnover. Preliminary studies suggested circulating levels of RPs were associated with cardiovascular events (CVEs) in patients with coronary artery disease (CAD). Methods: This study systematically searched PubMed, Scopus, Embase, and Web of science for eligible studies which reported RPs as a prognostic factor and the incidence of CVEs in CAD patients. The risk estimates and 95% confidence intervals (95% CI) were analyzed for adjusted and unadjusted associations separately using random-effects model. Meta-regression and subgroup analysis were used to identify the source of heterogeneity. Funnel plots, Egger’s test and trim and fill methods were used to assess the publication bias. Results: A total of 6 cohort studies were included in this meta-analysis. Four studies were rated as high quality with the remaining rated as moderate quality. The funnel plot, Egger’s test and trim and fill method suggested the presence of publication bias. The pooled results indicated elevated RPs were associated with a higher risk of composite CVEs (risk ratio [RR]: 2.26, 95%CI:1.72-2.98, with little heterogeneity) and cardiovascular death (RR: 2.33, 95%CI:1.66-3.28, with little heterogeneity). Based on results of separate meta-analysis, we found RPs might be a good predictor for revascularization but not for myocardial infarction or cerebrovascular events. After adjustment of conventional prognostic factors, the pooled result still suggested the prognostic value of RPs for composite CVEs (RR:2.00, 95%CI:1.30-3.08, p<0.00001, with substantial heterogeneity). Subgroup analysis and meta-regression of adjusted risk estimates revealed that the number of adjustment factors might be the source heterogeneity. Conclusion: Circulating level of RPs might be a useful prognostic marker for CVEs in CAD patients, even after adjustment of other prognostic factors